Pengaruh Personal Branding Terhadap Purchase Intention Yang Dimediasi Oleh Influencer Credibility Pada UMKM Kota Surabaya - Tania, Jesslyn Beatricia Ivana; Sitepu, Sri Nathasya Br (Gorontalo Management Research, 2024)
MSMEs in Surabaya City are business sectors in the city of Surabaya which are categorized into two fields, namely: food and non-food fields. The study used three variables including: personal branding variables, purchase intention and influencer credibility. The purpose of the study was to analyze the influence of personal branding on purchase intention mediated by influencer credibility in MSMEs in Surabaya City. This study used a nonprobability sampling technique with a sample of 108 people. This research is included in quantitative research using the PLS-SEM method. This study has several findings including: 1) personal branding affects influencer credibility, 2) influencer credibility affects purchase intention. The results of the study concluded that the availability of personal branding from MSMEs is important to provide.